Desenvolvimento de metodologias para localização de faltas em linhas de transmissão a partir de medidas não sincronizadas de dois terminais - Oliveira Neto, Moisés Honorato de (2018)
The Brazilian electric system formed by numerous transmission lines, that connect the centers of consumption to the centers of generation. When a permanent fault occurs on one of these lines, the work of the maintenance teams to locate the point of failure is usually time- consuming, which entails several financial losses, both for the consuming companies and for the concessionaire. The oil sector, for example, is one of the major impaired due to the shutdown of transmission lines that serve the extraction fields. In this sense, studies related to the location of faults in transmission lines have been very frequent in the literature. These studies have the general objective of determining precisely the location of the fault, assisting the maintenance teams in the rapid restoration of the energy supply. This work was intended to develop two methodologies for locating faults in transmission lines, both based on unsynchronized fundamental Fasos of two terminals. The methodologies presented two steps. In the first stage, called the processing stage, the voltage and current, synchronized, of the two terminals of the transmission line were obtained. In the second step, localization methodologies were implemented, developed from the concept of minimum squares. For the validation of the methods, there were simulated, in the ATP software, faults in different transmission lines. The performances of the localization algorithms were therefore evaluated considering short circuits in several locations of the line, and for different resistances of lack. The results obtained showed that the developed methodologies are accurate and represent important tools to compose the state of the art of locating faults in transmission lines